2014
DOI: 10.15236/ijcpd.2014.10.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of a New Mouthwash Containing Essential Oil of Cardamom in Reducing Volatile Sulphur Coumpounds Concentration

Abstract: The aim of this study was to assess the clinical efficacy of new mouthwash based on kapulaga fruit (Amomum cardamommum L.) containing 0.5% essential oil and compared to 0.5% Listerine Ⓡ as a positive control and placebo in reducing volatile sulphur compounds (VSCs) concentration of halitosis subjects. Methods: A randomized, double blinded, cross-over design was conducted among 20 healthy volunteers in Medan, Indonesia. Subjects were divided into 3 groups (Cardamom, Listerine Ⓡ , placebo group) and instructed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…More specifically, Souiss et al reported that cardamom inhibits the growth of periodontal pathogens such as: P. gingivalis, P. intermedia, and Aggregatibacter actinomycetemcomitans; those bacteria are highly associated with production of halitosis [ 38 ]. In a clinical trial, Erawati et al stated that rinsing with a mouthwash containing 0.5% cardamom essential oil had reduced the levels of VSC in breath for up 5 h after rinsing [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Souiss et al reported that cardamom inhibits the growth of periodontal pathogens such as: P. gingivalis, P. intermedia, and Aggregatibacter actinomycetemcomitans; those bacteria are highly associated with production of halitosis [ 38 ]. In a clinical trial, Erawati et al stated that rinsing with a mouthwash containing 0.5% cardamom essential oil had reduced the levels of VSC in breath for up 5 h after rinsing [ 39 ].…”
Section: Discussionmentioning
confidence: 99%